Inhibited symptoms of Reactive Attachment Disorder: links with working models of significant others and the self. Issue 2 (4th March 2019) - Bosmans, Guy; Spilt, Jantine; Vervoort, Eleonora; Verschueren, Karine
ABSTRACT: To better understand Reactive Attachment Disorder (RAD), the current study tested whether emotionally and behaviorally disordered children with versus without RAD differ with regard to the quality of their interpersonal behavior during interactions with teachers and with regard to their representations of self and others. Therefore, 77 children were screened for RAD symptoms and 22 likely cases of inhibited RAD were identified. To measure quality of the interactions with teachers, we observed children's trust and positive affect in dyadic interactions with teachers. For the representations of others, we measured self-reported trust in parents and teachers. For the representations of the self, two self-esteem assessments were individually administered. Results showed that, compared to children with other emotional and behavior disorders, RAD children's behavior reflected less trust in their teachers. At the level of representations, children reported less trust in teacher care. Instead, no links were found with self-report measures focusing on representations of parents and of self. These findings will be discussed in light of the ongoing discussion about whether or not attachment disorder and insecure attachment are associated concepts.